Anderson impurity model: Vertex corrections within the finite U non-crossing approximation - Roura Bas, Pablo Gines (2009)
We revise the simplest possible approximations to solve numerically the vertex equations for the Anderson Impurity Model within the finite U Non-Crossing Approximation (UNCA) considering the self energies at lowest order in 1/N, that is, within the (1/N)^0 diagrammatic expansion. We introduce an approximation to the vertex corrections that includes the double energy dependence and compare it with an approximation (NCAf2v) that neglects a second energy argument. Finally, we analyse the influence on the estimated Kondo scale for simple electronic models.